2004
DOI: 10.1111/j.1600-6143.2004.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein and Body Mass Index Independently Predict Mortality in Kidney Transplant Recipients

Abstract: C-reactive protein (CRP) is a risk factor for cardiovascular outcomes and mortality in the general population.To date, there are no prospective studies of the association between CRP and mortality or allograft loss in kidney transplant recipients (KTR). In 1995, 438 consecutive KTR were enrolled in this prospective study. Important information on demographic, clinical and immunological characteristics was collected at baseline, and CRP was measured using standard methods. Patients were then followed-up for a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 29 publications
5
44
1
Order By: Relevance
“…An elevated concentration of C-reactive protein (CRP) is independently associated with increased risk for CVD events in transplant recipients (63). This finding is consistent with studies in the general population demonstrating an association between CRP and ischemic heart disease.…”
Section: C-reactive Proteinsupporting
confidence: 79%
“…An elevated concentration of C-reactive protein (CRP) is independently associated with increased risk for CVD events in transplant recipients (63). This finding is consistent with studies in the general population demonstrating an association between CRP and ischemic heart disease.…”
Section: C-reactive Proteinsupporting
confidence: 79%
“…By dichotomizing the CRP at 0.5 mg/dl, Winkelmayer et al showed that renal transplant patients above that level had a 53% increased mortality risk compared with patients with a CRP below the threshold (22). In a subsequent paper, Winkelmayer and colleagues demonstrated a J-shaped association between hsCRP and mortality in kidney transplant recipients when dividing hsCRP values into quartiles for values below 5 mg/L.…”
Section: Discussionmentioning
confidence: 91%
“…The IL-6 data are more difficult to assess across diverse populations because of lack of standardized methods (31). However, in the posttransplant recipients, the inflammatory markers CRP and IL-6 have been reported to be elevated in most studies on renal transplant recipients (19,(21)(22)(23)(32)(33)(34)(35)(36), although they are lower than pretransplant values (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-sensitivity C-reactive protein (hsCRP) has been found to be independently associated with major CV events and allcause mortality in RTRs [135,136] , although this is not supported unanimously by all studies [137] . Those with a CRP > 5 have an increased mortality compared to patients below that threshold [138] and there is a Jshaped association between hsCRP and mortality suggesting that RTRs with very low hsCRP may also be at increased risk of death [139] . More novel markers such as asymmetric dimethylarginine, which is associated with endothelial dysfunction, are also associated with higher risk of mortality (HR = 2.18) and developing CVD (HR = 2.59) in ESRD [140] .…”
Section: Inflammationmentioning
confidence: 99%